Enhancing primary care and preventive services through Interprofessional practice and education - Terri Fowler; David Garr; Natalie Di Pietro Mager; Joan Stanley (BMC, 2020)
Abstract Interprofessional (IP) practice and education are important when seeking to respond to the growing demand for primary and preventive care services. Multiple professions with synergistic expertise are needed to effectively provide health promotion, disease prevention, and patient education and to help patients with multiple comorbidities, chronic health conditions, and care coordination. A recent study by Schor et al. titled, "Multidisciplinary work promotes preventive medicine and health education in primary care: a cross-sectional survey," compares the implementation of preventive services in three primary care models. Higher rates of health services, patient education, and health outcomes were documented in two different models of care involving persons in multiple professions when compared with independent solo physicians' practices. In this commentary, we focus on the value of IP team-based care, continuing professional development, and the impact of the team on practice performance and health outcomes. Key components of effective IP teams include using consistent terminology to describe the team composition and function, team structures with purposeful selection of professions to address gaps in care, leadership support, and IP continuing professional development and education.